KEANEKARAGAMAN TUMBUHAN SELAGINELLA DI KAWASAN BUKIT GATAN KABUPATEN MUSI RAWAS - Eli Suryani; Yuli Febrianti; Destien Atmi Arisandy (Nusantara Hasana Journal, 2023)
This study aims to determine the species of Selaginella plants in the Bukit Gatan Area of ​​Musi Rawas Regency, to determine the diversity index, domination index, evenness index, and relative density index of Selaginella plants in the Bukit Gatan Area of ​​Musi Rawas Regency. The research method used is descriptive qualitative. The data collection technique in this study used the roaming method and purposive sampling techniques. Based on the results of research on the diversity of Selaginella plants in the Bukit Gatan Area, Musi Rawas Regency, 1035 Selaginella plants of 9 species were found. The results of the analysis of the diversity index of Selaginella plants were categorized as moderate, the domination index value of 0.162 was categorized as low, the species evenness index value of 0.903 was categorized as high and the KR value of 99.998% was categorized as high. Soil pH in the Bukit Gatan area of ​​Musi Rawas Regency ranges from 6-7, air temperature ranges from 27°C-30°C, soil moisture ranges from 2% -6%, and light intensity ranges from low to high. So it can be concluded that research in the Bukit Gatan area of ​​Musi Rawas Regency contained 9 types of Selaginella plants and had moderate diversity, low dominance, high species evenness analysis results and relatively high density and had neutral soil pH, normal air temperature, dominant soil moisture medium and low dominant light intensity.